Ways of walking : ethnography and practice on foot - Ingold, Tim; Vergunst, Jo Lee (Aldershot : Ashgate publishing, 2008)
Before a step too far / Lye Tuck-Po -- Walking stories / Allice Legat -- The dilemmas of walking / Thomas Widlok -- Feet following hooves / Pernille Gooch -- Performing on the landscape versus doing landscape / Kenneth R. Olwig -- Listen to the sound of time / Katrin R. Olwig -- Listen to the sound of time / Katrin Lund -- Taking a trip and taking care in everyday life / Jo Lee Vergunst -- Walking through ruins / Tim Edensor -- Walking out of the classroom / Elizabeth Curtis -- Enchantment engineering and pedestrian empowerment / Sonia Lavadinho and Yves Winkin -- Taking a line for a walk / Raymond Lucas -- A collectable topography / Hayden Lorimer and Katrin Lund.
Onderzoek KASK (1KA-OFWC)
boek